2017
DOI: 10.1089/jamp.2016.1336
|View full text |Cite
|
Sign up to set email alerts
|

Regional Ventilation Is the Main Determinant of Alveolar Deposition of Coarse Particles in the Supine Healthy Human Lung During Tidal Breathing

Abstract: These results support the hypothesis that alveolar deposition is directly proportional to ventilation for ∼5 μm particles that are inhaled in the supine posture and are consistent with previous simulation predictions that show that convective flow is the main determinant of aerosol transport to the lung periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
1
1
0
1
Order By: Relevance
“…In the supine position in healthy spontaneously breathing humans, alveolar deposition of aerosols is seen to be directly proportional to ventilation with increased deposition in the lower lobes. 35 Our study shows similar deposition patterns in mechanically ventilated sheep.…”
Section: Discussionsupporting
confidence: 76%
“…In the supine position in healthy spontaneously breathing humans, alveolar deposition of aerosols is seen to be directly proportional to ventilation with increased deposition in the lower lobes. 35 Our study shows similar deposition patterns in mechanically ventilated sheep.…”
Section: Discussionsupporting
confidence: 76%
“…3) Согласно клиническим рекомендациям при бронхиальной астме для доставки при помощи небулайзера используются бронходилататоры и глюкокортикостероиды [6]. Применение суспензии будесонида нацелено на быстрое и безопасное купирование дневных и ночных симптомов при обострении бронхиальной астмы [7][8][9][10][11].…”
Section: небулайзерная терапия при бронхиальной астмеunclassified
“…In healthy subjects, we showed that peripheral deposition and ventilation are proportional. (79) Combining quantitative MR ventilation imaging with particle deposition measurements has the potential to enable the early evaluation of inhalable drugs and contribute to optimization of their targeted delivery through manipulation of actionable characteristics such as resident gas properties, time/depth of inhalation, and particle size.…”
Section: Pulmonary Delivery Of Gasesmentioning
confidence: 99%